Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 5 - Section 5.5 - The Substitution Rule - 5.5 Exercises - Page 419: 17



Work Step by Step

$$A=\int\frac{e^u}{(1-e^u)^2}du$$ $$A=\int e^u(1-e^u)^{-2}du$$ Let $r=1-e^u$. Then $dr=-e^udu$, so $e^udu=-dr$ Substitute into $A$, we have $$A=-\int r^{-2}dr$$ $$A=-\frac{r^{-1}}{-1}+C$$ $$A=\frac{1}{r}+C$$ $$A=\frac{1}{1-e^u}+C$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.